Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Akidah Akhlak Materi Islam Washatiyah Kelas X di Madrasah Aliyah Proyek UNIVA Medan - Berampu, Wantri Anggraini; Ritonga, Asnil Aidah; Pulungan, Juli Julaiha (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study identifies problems related to the lack of ability of moral faith teachers to apply various learning models, which is caused by a lack of information about these models. Learning activities in the classroom are often limited to listening and lecture methods. Referring to the Musdalipa cooperative learning model guidebook, the snowball throwing model has proven to be effective in increasing students' knowledge and ability to interact. Therefore, this study aims to explore the influence of the snowball throwing type cooperative learning model on the learning outcomes of moral beliefs in class X Madrasah Aliyah UNIVA Medan Project. The methodology used is a quantitative approach with a quasi-experimental design of a nonequivalent control group. The study population included all students in grade X, with a sample of 45 students divided into experimental and control groups. The instrument used to collect data is a multiple-choice test to assess student learning outcomes. The data analysis technique was carried out using a parametric t test, an independent sample t test, which must first meet the prerequisite tests for analysis in the form of normality and homogeneity tests. The results of the analysis show that the significance value of the calculation is greater than the table, namely: 13.406 > 1.68195 and Sig. (2 tailed) = 0.000 < 0.05, then H0 is rejected and Ha is accepted. Thus, there is a significant influence of the snowball throwing model on the learning outcomes of students' moral beliefs. This study concludes that the application of this model can improve learning outcomes, so it is recommended that education stakeholders provide training to teachers on various learning models.